Acute Onset Sclerosing Peritonitis after Laparoscopic Hysterectomy- A Rare Case with Review of Literature - Himleena Gautam, MBBS, MS, DNB, FMAS; Mrinal Chandra Bhattacharyya, MBBS, MD; Mukesh Agarwal, MBBS, MD, DM; Nilom Khound, MBBS, MD; Dipak Prasad Das, MBBS, MS; Kamal Kumar Kathar, MBBS, DGO (British Journal of Healthcare and Medical Research, 2023)
Sclerosing peritonitis (SP) is a rare condition in which peritoneal inflammation leads to sclerosis and fibrosis of peritoneum with ultimate encapsulation of the small bowels leading to mechanical obstruction. This entity is mostly described after chronic peritoneal dialysis and acute onset is very rare. Though many risk factors have been described, there are many idiopathic cases too. In this article, we describe a case of sclerosing peritonitis which develops within a span of 1month after total laparoscopic hysterectomy and bilateral salpingo-ophorectomy. Previously only one case of sclerosing encapsulating peritonitis has been described after abdominal hysterectomy, but its course was chronic. Surgery with minimal adhesiolysis followed by use of steroids and immunosuppressants was the treatment given in our case, which resulted in good clinical outcome. SP is not common and literature is mostly confined to case reports and case series.